GAMBARAN PERILAKU BULLYING PADA MAHASISWA UMN ALWASHLIYAH - Shavreni Oktadi Putri; Beta Rapita Silalahi (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2017)
Bullying behavior phenomenon that is conducted by students are getting apprehensive lately, that because education institutions are as the places to educate people turn into bullying behavior spot including university students. Bullying means as an attempt which is conducted to harm a group or a person. Therefore, the purpose of this study is to find out levels and kinds of bullying that happened among UMN Al Washliyah Students. Research subject were 102 students of UMN at education of early childhooddepartment that were taken from 4 classes by using cluster random sampling method. Data collection was conducted by using bullying scale from Colloroso. Data analysis method by using Pearson product moment and descriptive statistic. The results of study show that (1) the level of bullying behavior which is done by students is at the medium category with the percentage 74,5%. (2) kindof bullying behaviors which are done most by students is verbal bullying with the percentage73.5% and (3) bullying behaviorthat is done very often by students in 7th semester is 83,9%.